Rancang Bangun Alat Pendeteksi Ketinggian Air Banjir Berbasis Arduino Uno - ROSIDIN, MOCHAMMAD KHOIRUL ROSIDIN; Farhan, Ahmad Farhan; Ilman, Syaeful Ilman; Alba Pradana, Claudha; Irawan, Candra; hadi, bagus dharmawan hadi; rahajeng , rahajeng kurnianingtyas; suhanto, rhesti n suhanto (Politeknik Negeri Indramayu, 2025)
Floods are a disaster that often hits urban areas in Indonesia, especially due to high rainfall and inadequate drainage systems. To reduce the risk of flooding, an effective and automatic early warning system is needed. This study aims to design and develop an air flood height detector based on an Arduino Uno microcontroller with the integration of an HC-SR04 ultrasonic sensor, servo motor, I2C LCD, buzzer, and LED indicator. This system is able to detect air height in real time, display information on the LCD, provide visual and audio warnings, and automatically adjust the position of the air door based on the detected air height level. The test results show that this tool works with high accuracy (error rate <2%) and can respond to changes in air height quickly. This system successfully automates water flow management and provides information that can be used for flood mitigation. Potential future developments include integration with IoT technology and mobile applications for remote monitoring